Використання спектроскопії та комп'ютерного моделю-вання для вивчення поверхонь, модифікованих іонною імплантацією - Nikolaieva, D.Yu.; Honcharov, V.V.; Ivashin, D.Yu.; Zazhigalov, V.O. (Publishing house "Academperiodika", 2021)
Using X-ray Photoelectron Spectroscopy (XPS) and energy dispersion spectrometry, the phase and elemental compositions of the nanoscale surface layer of implants are studied. The method of determination of the optimal mode of nanoscale modification of the surfaces of metals and alloys by means of the ionic implantation is presented. The problem of processing the curved surfaces with mathematical calculations and a computer simulation is solved. The proposed technique is tested on synthesized implants. The sample hardness was taken as a criterion.